2023
DOI: 10.1021/acs.nanolett.3c03062
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free Hydrazinium Halide Perovskitoid Single Crystals for X-ray Detection

Zhizai Li,
Shenghuan Shi,
Guoqiang Peng
et al.

Abstract: Metal-free perovskitoids (MFPs) with N2H5 + as B-site component possess higher crystal density and hydrogen bonding networks and have been recently expanded into X-ray detection. However, research on this material is in its infancy and lacks an understanding of the function of halide components on physical properties and device performance. Here, N2H5-based MFP single crystals (SCs) with different halides are fabricated, and the influence of halides on the crystal structure, band nature, charge transport chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Recently, a new X-ray detecting material of metal-free perovskite (MFP) single crystals (SCs) has met the green concept of nontoxic components and nontoxic aqueous solutions, which were prepared by introducing the B-site component of NH 4 + /N 2 H 5 + to replace the toxic metal cations of MHPs. At the same time, this simple component substitution can be compatible with the flexibility and lightweight characteristics of organic materials and exhibit excellent optoelectronic properties for the SC-type MFPs with less trap density and grain boundary. , Moreover, the recently reported MFP SCs only showed a slightly inferior mobility–lifetime (μτ) product than the MHPs including 3D MAPbI 3 , which drives their application in the X-ray detection field. In 2020, the first MFP-based X-ray detector was developed by Zhao et al, who found that the MFPs of DABCO-NH 4 Br 3 (DABCO = N–N′-diazabicyclo[2.2.2]­octonium) SC possessed high carrier diffusion lengths (tens of μm), while exhibiting enough X-ray attenuation capabilities and lightweight properties with an X-ray detection sensitivity of 173 μC Gy air –1 cm –2 . Subsequently, different MFP SCs have been actively explored and expanded for X-ray applications, somewhat advancing this field. …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a new X-ray detecting material of metal-free perovskite (MFP) single crystals (SCs) has met the green concept of nontoxic components and nontoxic aqueous solutions, which were prepared by introducing the B-site component of NH 4 + /N 2 H 5 + to replace the toxic metal cations of MHPs. At the same time, this simple component substitution can be compatible with the flexibility and lightweight characteristics of organic materials and exhibit excellent optoelectronic properties for the SC-type MFPs with less trap density and grain boundary. , Moreover, the recently reported MFP SCs only showed a slightly inferior mobility–lifetime (μτ) product than the MHPs including 3D MAPbI 3 , which drives their application in the X-ray detection field. In 2020, the first MFP-based X-ray detector was developed by Zhao et al, who found that the MFPs of DABCO-NH 4 Br 3 (DABCO = N–N′-diazabicyclo[2.2.2]­octonium) SC possessed high carrier diffusion lengths (tens of μm), while exhibiting enough X-ray attenuation capabilities and lightweight properties with an X-ray detection sensitivity of 173 μC Gy air –1 cm –2 . Subsequently, different MFP SCs have been actively explored and expanded for X-ray applications, somewhat advancing this field. …”
mentioning
confidence: 99%
“…However, the MFPs rely solely on hydrogen bonding to connect the components, which makes the materials and devices less stable under high-energy X-ray irradiation. , To solve this problem, A-site molecular functionalization strategies have been proposed in recent years. , This method is used to obtain a larger radius of the A-site cation by functionalization, which improves the tolerance factor to an ideal value of the MFPs and further enhances the materials’ stability . However, a larger angular bending between chemical bonds should be realized to accommodate larger organic cations in MFPs, which would distort the crystal structure of their materials to a certain extent, limiting their device performance. , Moreover, the introduction of larger-sized A-site components could affect the crystal quality and crystal growth, thus limiting the physical properties of the crystals. Notably, the distorted crystal structure and poor crystal quality could influence the transport of carriers and result in the degradation of device performance. , Therefore, the stability of MFPs and their device performances must be balanced and considered when larger radii of A-site components are introduced. Moreover, although the methyl, hydroxyl, and amino functional groups have been successfully used to modify the A-site organic cations for effective X-ray detection, their effects on crystal structure and photoelectronic properties are still poorly investigated, especially in lattice distortion and crystal growth. ,,,, Therefore, these compel us to develop or explore new organic cations to achieve an improvement in the material stability and device performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation